STUDI PENGETAHUAN DAN SIKAP TINDAKAN MAYARAKAT TERHADAP SANITASI LINGKUNGAN DI PANTAI BALLONA KECAMATAN TALIWANG KABUPATEN SUMBAWA BARAT - DEWI, NI MADE NIA BUNGA SURYA (GANEC SWARA, 2021)
Sanitation is a control over all factors of the human physical environment which can / can have adverse effects on human life, both physically and mentally. Environmental cleanliness is closely related to the health of the surrounding community, various problems are often caused by a lack of information received by the community. The results of research using this descriptive method are to describe the knowledge, attitudes and actions of the community on the coast of Ballona beach Taliwang District, West Sumbawa Regency regarding environmental sanitation, which was carried out in September - October 2020 in Taliwang District for 97 respondents and data collection methods. which is used is the use of methods of observation (observation) and interviews (questionnaire and SPSS as  a  research instrument.       People who live on the coast  of Ballona beach Taliwang district which have good knowledge about sanitation are    39  respondents (40.2%),  which has sufficient knowledge of 51 respondents (52.6%) and  7 respondents (7,2%) who have poor knowledge of sanitation. Meanwhile, the coastal communities of Ballona beach Taliwang District who had positive attitudes towards sanitation were 46 people (47.4%) and negative respondents were 51 (52.6%) people and 0 respondents who had good actions regarding environmental sanitation. There were 34 respondents (35.1%) who had sufficient action in the coastal area of the coast of Taliwang District and 63 respondents (64.9%) had unfavorable actions.